PENGARUH KOMPETENSI DAN MOTIVASI INTRINSIK TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA STUDI PADA GURU SMA NEGERI DI WILAYAH TIMUR KABUPATEN PEMALANG - Indah Aryani, 12 5202 0143; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study examined the Effects of Competence and Intrinsic Motivation on Performance Teacher intervened by job satisfaction (Case study in SMA Negeri in Pemalang ). The specific objectives of the study is to examine how the the effects of Competence and Intrinsic Motivation on Performance Teacher intervened by job satisfaction (Case study in SMA Negeri in Pemalang) . The purpose of this study is to explain and extend previous research on the Effects of Competence and Intrinsic Motivation on Performance Teacher intervened by job satisfaction. The population in this study were high school teachers in Pemalang. The samples of 116 teachers were determined using the Slovin formula and Proportional Random Sampling technique. In this study used primary data obtained by questionnaire. The research using questionnaire in a question form of high school teachers in Pemalang. This method research using computerized approach to the statistical program SPSS (Statistical Package for Social Science). The method of data analysis used linear regression to test an intervening. The results shows that competence has a positive and significant impact on teacher performance. Intrinsic motivation has not significant effect on job satisfaction. Competence has a positive and significant impact on performance of teachers. intrinsic motivation is not significant on teachers performance. Job satisfaction has a positive and significant on teacher s performance . Keywords : competence, intrinsic motivation, job satisfaction and mediation .